Mycetia hirta Hutch. (Rubiaceae), a new record for the flora of Vietnam - Vu Tien Chinh; Nguyen Quoc Binh; Tran Van Hai (Vietnam Journal of Science, Technology and Engineering, 2020)
A newly recorded species, Mycetia hirta Hutch. (Rubiaceae) was reported from Muong Phang district, Dien Bien province in northern Vietnam. It is distinguished from the closely related species, M. longifolia, by its hairy stem and leaf blades, much shorter corolla tube and hirtellous calyx and corolla. Morphological description and color photographs of M. hirta Hutch. are provided.